Nonadherence is Associated with Lack of HIV-Related Knowledge: A Cross-Sectional Study among HIV-Infected Individuals in Guinea-Bissau. (July 2016) - Dyrehave, Charlotte; Rasmussen, Dlama Nggida; Hønge, Bo Langhoff; Jespersen, Sanne; Correia, Faustino Gomes; Medina, Candida; Wejse, Christian; Rodkjaer, Lotte; ,
Background: Poor treatment adherence is a main barrier for effective antiretroviral therapy (ART) globally. HIV-related knowledge may affect understanding and utilization of HIV medical information, hence limited health literacy is a known barrier to treatment adherence. Design and Methods: A cross-sectional study included 494 HIV-infected individuals from the Bissau HIV Cohort in Guinea-Bissau. They completed a questionnaire designed for assessment of adherence and HIV-related knowledge. Results: A majority were female, 41% were illiterate, 25% did not take the medicine during the last 4 days, and 23% skipped their medicine during weekends. The most frequent reasons for not taking medicine were simply forgetting, side effects, lack of food, and being too ill to attend the clinic. Nonadherent patients had a lower level of HIV-related knowledge. Conclusion: Main barriers for nonadherence were side effects, food insecurity, and simply forgetting. Lack of HIV-related knowledge about ART and HIV may be a barrier to nonadherence.